English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x - 3y= 2
-5x + 2y= -16

and

3x + 5y= -19
5x - 2y= 20

it says to find the values of x and y.
i tried doing the first set and got -2 for x and y, when i put it into the computer it said that was wrong, so i was to frustrated to even attempt the second problem.

2007-10-28 11:52:14 · 7 answers · asked by Lilly 2 in Science & Mathematics Mathematics

7 answers

its simple once u get the hang of it

2x-3y= 2

wat u need to do is break the problem into smaller problems

2 * ? - 3 * ?=2

2*4= 8
3*2=6

8-6=2
therefore x= 4 and y=2

hope this helps........good luck

2007-10-28 11:56:51 · answer #1 · answered by Show Stoppin 1 · 0 0

i don't know if you were given any particular instructions as to how to find the values of x & y...if you were not given any specific instructions, here goes one method .......it's called "by elimination."

step 1....decide which variable you would like to eliminate....it's purely your choice..........i'd choose "y" because the "y's" already have opposite signs.

step 2.....multiply equation 1 by some factor that will allow you to eliminate "y" when you add it to equation 2........since "y" in equation 2 does not equal to any factor of "2", the coefficient of "y" in equation 1, then you will have to multiply equation 2 also by some factor that will allow "y" to be eliminated............in other words, multiply equation 1 by 2 and equation 2 by 3 in the following manner.

2[2x - 3y = 2] ==> 4x - 6y = 4
3[-5x + 2y = -16] ==> -15x + 6y = -48

Step 3..........now you can add the 2 equations together and notice that the "y's" go out.

so you get.........-11x = -44..........and thus x = 4

Step 4...........substitute 4 back into either equation 1 or 2.......i'll substitute into equation 1

2(4) - 3y = 2 ===> 8 - 3y = 2 ===> -3y = -6 ===> y = 2

therefore, your answer should be x = 4, y = 2...............

try your hand at the next problem........(hint: eliminate y by multiplying eq 1 by 2 and eq 2 by 5)...........if you run into probs, email me..................ciao

2007-10-28 12:11:58 · answer #2 · answered by ms teech 1 · 0 0

2x - 3y= 2 <-- Eq 1
-5x + 2y= -16 <-- Eq 2
Multiply Eq 1 by 2 and Eq 2 by 3 getting:
4x-6y =4
-15x +6y =-48
Add the above two new equations getting:
-11x = -44
x = 4
2(4) -3y = 2
8-3y = 2
-3y = -6 --> y = 2

3x + 5y= -19 <-- Eq1
5x - 2y= 20 <-- Eq 2
Multiply Eq 1 by 2 and Eq 2 by 5 getting:
6x+10y =-38
25x -10y 100
Add the above two new equations getting:
31x = 62
x = 2
5(2) -2y = 20
10-2y = 20
-2y = 10
y = -5

2007-10-28 12:03:16 · answer #3 · answered by ironduke8159 7 · 0 0

u hav to use substitution or elimination...

1st ... 2x=3y +2
then u gotta divide each side by 2..
then substitute

same for the other

2007-10-28 11:55:35 · answer #4 · answered by blue.camo 2 · 1 0

get tutor online.

but with this, you just set the coefficients to equal the same thing and solve for one variable at a time. or plug in variables.

2007-10-28 11:55:45 · answer #5 · answered by geml0vely888 3 · 0 0

(1)
4x - 6y = 4
-15x + 6 y = -48
_____________
-11x = - 44 => x = 4 & y = 2


(2)
6x + 10y = -38
25x - 10y = 100
_____________
31x = 62 => x = 2 & y = -5

2007-10-28 11:58:54 · answer #6 · answered by Egemen 2 · 0 0

1st problem :: y = 2 and x = 4

2nd problem :: y = -5 and x = 2

2007-10-28 11:59:04 · answer #7 · answered by amakram 1 · 0 0

fedest.com, questions and answers